El Tribunal de Justicia de la Comunidad Andina y la singularidad del proceso de integración andino (Tema Central) - Mendoza Neyra, Yolanda (2020)
The bodies and institutions of the Andean Integration System are the ones that really design, guide, regulate and ensure the consolidation of the Andean Community. From there arises our interest in analyzing one of them, whose existence is essential for the supranationality of the Andean integration process. We refer to the Andean Court of Justice. In this article we argue that both its judicial activity and the Andean legal system mark the distance from the European integration process, and thus provide identity and singularity to the Andean integration, making it unique when comparing both processes.